Effect of Antioxidant Agents After Dental Bleaching on Color Stability and Mechanical Properties of Bonding Interface Components in Ceramic Laminate Veneer Luting - Strazzi-Sahyon, H. B.; Seixas, D. A.; Maluly-Proni, A. T. [UNESP]; Briso, André Luiz Fraga [UNESP]; Yoshimura, H. N.; Constantino, Cjl [UNESP]; Santos, Paulo Henrique dos [UNESP] (Operative Dentistry, 2023)
PURPOSE: Few studies have evaluated the influence of antioxidant agents on the optical and mechanical properties of ceramic laminate veneers after dental bleaching. Thus, this in vitro study aimed to evaluate the influence of antioxidant agents on the color stability and mechanical properties, such as nanohardness (HIT), elastic modulus (Eit*), and degree of conversion (DC) of the bonding interface components after dental bleaching in ceramic laminate veneer luting. METHODS AND MATERIALS: A total of 143 bovine teeth were distributed into experimental groups, according to the procedure method (unbleached or bleached with Whiteness HP Maxx 35%), antioxidant type (control, 10% ascorbic acid, or 10% α-tocopherol), and luting period (24 hours or 14 days) (n=13). The Tetric N-Bond Universal adhesive system and Variolink Esthetic LC resin cement were used as luting agents to lute IPS e.max ceramic restorations (0.6 mm in thickness) to enamel. A UV-visible spectrophotometer was used to assess color stability before and after UV-B artificial accelerated aging for 252, 504, and 756 hours (n=8). The HIT and Eit* of the adhesive and resin cement were measured using a nanohardness tester under a load of 1000 μN, and the DC was measured using a micro-Raman spectrometer (n=5). The color stability and mechanical properties were measured and evaluated by twoway and one-way ANOVA, respectively, and Tukey test (α=0.05). RESULTS: Distinct aging periods exerted significant changes on the color stability of the restorations luted in enamel associated with ascorbic acid, bleached and unbleached, and the bleached enamel under no antioxidant agent action, for the experimental groups evaluated after 14 days (p<0.05). The use of the α-tocopherol antioxidant solution after the bleaching process for 24 hours did not alter the optical and mechanical properties of the adhesive interface of the laminate restorations compared to those of the control group (p>0.05). CONCLUSION: The use of a 10% α-tocopherol antioxidant solution produced promising results, suggesting that it could be mediately used after tooth bleaching to lute ceramic laminate veneers.